Saddle curvature association of nsP1 facilitates the replication complex assembly of Chikungunya virus in cells - Xinwen Miao; Michelle Cheok Yien Law; Jatin Kumar; Choon-Peng Chng; Yongpeng Zeng; Yaw Bia Tan; Jiawei Wu; Xiangfu Guo; Lizhen Huang; Yinyin Zhuang; Weibo Gao; Changjin Huang; et al. (Nature Communications)
Abstract Positive-sense RNA viruses, including SARS-CoV-1 and -2, DENV, and CHIKV, replicate in curved membrane compartments within host cells. Non-structural proteins (nsPs) critically regulate these nanoscale membrane structures, yet their curvature-dependent assembly remains elusive due to the challenges of imaging nanoscale interaction on curved surfaces. Using vertically aligned nanostructures to generate pre-defined membrane curvatures, we here investigate the impact of curvature on nsPs assembly. Taking CHIKV as a model, we reveal that nsP1 preferentially binds and stabilizes on positively curved membranes, with stronger accumulation at radii ≤150 nm. This is driven by hydrophobic residues in the membrane association (MA) loops of individual nsP1. Molecular dynamics simulations further confirm the improved binding stability of nsP1 on curved membranes, particularly when it forms a dodecamer ring. Together, nsP1 supports a strong saddle curvature association, with flexible MA loops sensing a range of positive curvatures in the x-z plane while the rigid dodecamer stabilizing fixed negative curvature in the x-y plane - crucial for constraining the membrane spherule neck during replication progression. Moreover, CHIKV replication enriches on patterned nanoring structures, underscoring the curvature-guided assembly of the viral replication complex. Our findings highlight membrane curvature as a key regulator of viral nsPs organization, opening new avenues for studying membrane remodeling in viral replication.